Effects of 12 weeks nutrition education on nutritional status in hemodialysis patients - Harin Rhee; KeumSook Jang; Sang Heon Song; Il Young Kim; Eun Young Seong; Soo Bong Lee; M.D IhmSooKwak (The Korean Society of Nephrology, 2012)
Protein-energy malnutrition is present in a large proportion of patients with end stage renal disease and, is a strong risk factor for mortality in these patients. This study was aimed to evaluate the effectiveness of 12-weeks nutrition education during the hemodialysis session for the improvement of nutritional status. From the June 2011 to the September 2011, patients who were on regular hemodialysis in Pusan National University Hospital were enrolled in this study. In education group, intensive nutrition education was performed by the hemodialysis nurse, for fifty to sixty minutes during the hemodialysis session, once a week. Curriculum for renal nutrition includes regular taking of their medication, intake of moderate amount of protein and sufficient calories, reduction of water, salt, potassium and phosphate intake. Otherwise, any education program was not performed in patients of control group. Nutrition status was assessed by the subjective global assessment (SGA),body mass index (BMI), triceps skinfold thickness (TSF), arm muscle area(AMC) and laboratory markers such as serum albumin, serum blood urea nitrogen(BUN) and hemoglobin(Hb) level before and after the education. Effect of nutrition education was analyzed using ANCOVA test. A total of 49 patients were enrolled in this study and nutrition education was provided to 25 hemodialysis patients. Their mean age was 57.20±15.49 in education group and 55.13±14.42 in control groupand male was 56.0% in education group and 50.0% in control group and, other baseline characteristics were not significantly different between two groups. After the 12-week education, significant improvement was found in SGA, serum albumin, BUN and Hb level. SGA score was improved from 6.36±0.99 to 6.72±0.61 in education group, compared to control group(6.38±0.88 to 6.42±0.88, p=0.029 ). Improvement of serum albumin level, BUN and Hb was as follows: serum albumin(4.23±0.28 to 4.30±0.25 in education group, 4.28±0.39 to 4.13±0.34 in control group, p=0.040), serum Hb(10.45±1.49 to 11.13±1.74 in education group, 10.51±1.12 to 10.04±1.02 in control group, P=0.004), serum BUN(66.52±18.76 to 70.94±17.26 in education group, 59.50±13.61 to 58.68±13.88 in control group, p=0.032). 12 week nutrition education during the hemodialysis session by hemodialysis nurse was effective